Implementasi Akad Syirkah pada Usaha dengan Merk Dagang De Perfect Skincare - Maharati, Cindy (FADZAT: Jurnal Ekonomi Syariah, 2023)
This research discusses the implementation of the syirkah contract in a business with the trademark "De Perfect Skincare". Syirkah is a form of partnership in Islamic law where two or more parties share capital, expertise and responsibility in a business. This research is in-depth about how the syirkah contract is applied in the context of the increasingly growing skin care business, especially under the "De Perfect Skincare" brand. Through an Islamic legal analysis approach and case studies, this research investigates the legal and practical aspects of the syirkah contract, as well as its impact on the sustainability and success of this business. The findings in this research show that De Perfect Skincare for syirkah goes through many processes that are not easy. His thinking is about a business that is supported by the concept of sharia and aims not only to achieve profits in the world, but also to be safe in the afterlife and remain within the corridors of Islamic principles. Companies that are built apply Syirkah Akad, namely syirkah that occurs because there is an agreement between two or more parties for work (charity) and/or capital (mal) to obtain profits. The conclusion is that a business system based on sharia, in this case the syirkah system, is a system that really humanizes humans, because it upholds economic principles as well as sharia principles which are of course oriented towards the common good.